Radiation-induced optic neuropathy after stereotactic and image guided intensity-modulated radiation therapy (IMRT) - Brecht, Susan; Boda-Heggemann, Judit; Budjan, Johannes; Siebenlist, Kerstin; Stieler, Florian; Steil, Volker; Wenz, Frederik; Bürgy, Daniel (Radiotherapy and oncology, 2019)
Background/purpose - To quantify the risk of radiation-induced optic neuropathy (RION) after stereotactic/image-guided positioning and intensity-modulated radiotherapy (IMRT) with ≥50Gy to the anterior visual pathway (AVP). - Methods - Patients irradiated with ≥50Gy to the AVP using stereotactic/image-guided positioning between 2002 and 2011 in Mannheim were identified. Detailed dosimetric data were collected and patients or family members were retrospectively asked to rate visual acuity and visual disorders. - Results - 125 patients fulfilled the eligibility criteria. Average maximum equivalent point dose (Dmax-EQD-2[α/β=1.6]) to the AVP was 53.1±3.9Gy. 99 patients received ≥50Gy bilaterally (chiasm or both optic nerves), resulting in 224 (99x2 bilateral plus 26 unilateral) visual-fields-at-risk (VFAR) for RION. Eighty-two patients provided pre/post-IMRT visual status information (n=151 VFARs). Permanent visual deterioration occurred in 18 (22%) patients. In seven, visual deterioration was possibly related to radiotherapy (two-sided deterioration in one patient) for a crude incidence of 8.5% (7/82 patients) and 5.3% (8/151 VFARs). Two cases were caused by chronic keratitis/conjunctivitis; in five patients RION could not be excluded (one two-sided). In one of 13 patients with Dmax-EQD-2>58Gy, RION could not be excluded. In all affected patients, visual acuity post-IMRT had decreased only mildly (1-2 points on the 5-point-scale). One patient with relevant baseline visual impairment (3/5) developed unilateral blindness (crude incidence of blindness on patient-/VFAR-level: 1.2% and 0.66%; competing risk-adjusted/actuarial 24-month incidence: patient/VFAR-level: 1.8% and 0.95%). - Conclusion - Risk of RION was low in this cohort with accurate positioning and precise dosimetric information. Less conservative tolerance doses may be considered in patients with high risk of recurrence.